Latent tuberculosis infection in healthcare trainees: the need for structured occupational health surveillance in low-incidence countries - Paladino, Maria Emilia; Riva, Michele Augusto; Belingheri, Michael; Soriano, Antonio; Perconte, Claudio; Mattei, Federico; D'Orso, Marco Italo (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Latent tuberculosis infection (LTBI) remains a significant occupational health concern, even in low-incidence countries. Healthcare students and medical residents are exposed to Mycobacterium tuberculosis (MT) during clinical training, emphasizing the need for structured health surveillance. This study analyzes data from a health surveillance program for tuberculosis-related biological risk among healthcare trainees at a university hospital in Northern Italy (2018–2022), aiming to demonstrate the necessity of implementing systematic TB surveillance protocols. Methods: Data were collected from 2,087 healthcare students and medical residents undergoing routine tuberculin skin test (TST) screening, with interferon-gamma release assay (IGRA) confirmation for positive cases. Demographic characteristics, professional role, and vaccination history were analyzed. A multiple logistic regression model was used to assess factors associated with TST positivity. Results: Among the participants, 719 (34%) were male and 1,393 (66%) were female, with a mean age of 23.6 ± 4.5 years. TST was performed in 2,053 individuals (98.4%), and 52 (2.5%) tested positive. IGRA confirmed LTBI in 6 cases (11.5%). Logistic regression identified foreign nationality and older age as significant predictors of TST positivity, whereas sex and professional role were not associated. Conclusions: LTBI surveillance is essential for healthcare trainees, ensuring early detection, risk mitigation, and infection control. The findings support the implementation of structured TB health surveillance programs, reinforcing the key role of occupational physicians in protecting both trainees and patients. Establishing standardized protocols in low-incidence countries is crucial for reducing TB transmission risk and strengthening occupational health strategies. (www.actabiomedica.it)